The Campesino’s Early Actos as Templates for Today’s Students - Huerta, Jorge A. (Latin American Theatre Review, 2017)
In this article the author argues that actos, short political sketches created collectively by members of the Teatro Campesino, are just as relevant and necessary today as they were in 1965. After a brief introduction to the early Teatro Campesino, the article discusses the efficacy of satire and laughter as a weapon. He defines the acto as a genre, with roots in commedia dell’arte and other street-theatre forms. By describing the conventions of the form, he guides today’s students on how to create their own actos as effective and entertaining tools of theatre for social change. Using La quinta temporada (The Fifth Season) as a “quintessential acto” the author demonstrates how to make an audience laugh and think about social problems, offering potential solutions in today’s complex political climate.